The Impact of Tax Amnesty on Tax Revenue and Tax Ratio: Case in Indonesia - Sari, Diana; Mulyati, Yati (International Journal of Engineering and Technology, 2018)
The development of tax evasion in a country, often the problem solving is done by voluntary disclosure or tax amnesty. Both voluntary disclosure or tax amnesty seem to be a dilemmatic policy between the desire to uphold the rule of law by prosecuting tax smugglers on the one hand by imposing tax amnesty on the other which is viewed from a legal point of view which negates these claims legally. Tax amnesty is a counterproductive action in the tax sanctions system that regulates the waiver of prosecution or reduces or eliminates claims against penalties or fines contained in the provisions of taxation legislation. The positive side of the tax amnesty program is an increase in state revenues from the tax sector. However, an increase in tax revenues is not always followed by an increase in tax ratio.Â Â